Scada-Home Based Security System - Nurul Anis Nadia, Zahar (UTeM, 2009)
This project is about the design and the application of SCADA system for home automation and security system. It comprises the integration of various system that normally been used for efficient security system such as burglar alarm, fire detection, water sprinkler, lighting system and others. In this project, four sensors will be used which is connected to an alarm system. The equipment that intended to be used is Programmable Logic Controller (PLC), an alarm system and sensors. InduSoft WebStudio Project will be used in this project which will control all the system we want to monitor.